Sensory and Oxidative Stability of Roasted Peanuts Coated with Arabic Gum and A Synthetic Antioxidant During Storage - Aljaludi, Rawan; Alkhderat, Razan; Al-Dabbas, Maher (International Journal of Membrane Science and Technology, 2023)
The impact of coating formulations containing Arabic gum (AG) and Arabic gum with 100 ppm BHT on the oxidative stability and sensory attributes of roasted peanuts during a 120-day storage period at room temperature (RT) was investigated and compared to roasted, uncoated peanuts (control). The oxidative stability of raw peanuts (P), roasted peanuts (RP), roasted and coated peanuts with Arabic gum (RCP-AG), and roasted and coated peanuts with Arabic gum and 100 ppm BHT (RCP-AG-BHT) was determined based on parameters such as free fatty acids percentage (FFA%), peroxide value (PV), p-Anisidine value (pAV), Totox value (TV), and sensory properties at intervals of 0, 30, 60, and 120 days.The estimated coating percentage (CP %) for all treatments is about 2.5% and the yield of oil from hydraulic pressed peanuts kernels and treatments were ranged from 35.6 to 47.1%. Nine fatty acids were identified from raw and roasted peanuts oil and characterized by large percentage of unsaturated fatty acids (USFAs) (82.1 %) with large proportion of oleic acid (49.45%) and linoleic acid (31.92%), while saturated fatty acids were 17.9%, with large proportion of palmitic acid (11.36%) followed by stearic acid (3.48%) in RP. The FFA (%) of extracted raw peanuts oil was 0.68%, this percentage was increased after roasting significantly (p< 0.05) in all treatments and control, but it didn’t increase during storage period. An increase in PV values of roasted and treated samples were noticed throughout the storage time. After 4 months of storage, the maximum value of PV was (75.1 meq/kg) recorded by the roasted sample (RP), whereas the minimum value was (43.9 meq/kg) recorded by (RCP-AG- BHT). pAV increased significantly after roasting and during storage time in all peanuts samples. However, RP-AG-BHT showed no significant differences in pAV after one month of storage. An increase in TV values of roasted and treated samples were noticed throughout the storage time, while the TV for RP-AG and RP-AG-BHT where less when compared with the control (RP). There were no significant differences (P < 0.05) in the color, hardness and crunchiness between control and treatments after 2 months of storage. However, Glossiness, rancidity and off-flavor were significantly affected.